1976
DOI: 10.1111/j.1432-1033.1976.tb10951.x
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric Investigations on Thermal Stability of tRNAIle (Yeast) and tRNASer (Yeast)

Abstract: Variation with temperature of the partial heat capacities of tRNAIle (yeast) and tRNASer (yeast) has been determined in two buffers at various salt conditions by scanning microcalorimetry. The overall molar transition enthalpy, ΔHt= 320 ± 20 kcal mol−1 (1339 ± 84 kJ mol−1) is identical for the two tRNA species within the limits of experimental error. ΔHt does not show any dependence on the nature of the buffer, nor does' it vary on addition of 1 mM MgCl2 or 150 mM NaCl. Thermal unfolding of the native structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…They apparently also do vary between pH 6.5 and 7.0 and therefore can be expressed by the average value of AHt=298 15 kcal mol-' (1247 2 63 kJ mol-I). This transi- tion enthalpy is appreciably higher than the enthalpy values reported so far for tRNAYhe (yeast), but its magnitude is in excellent agreement with melting enthalpies recently determined for tRNA"' (yeast) and tRNASe' (yeast) [25]. Partial specific heat capacities normalized to 20 "C [ c i ]~~, are also consistent for these three tRNA's.…”
Section: Resultssupporting
confidence: 53%
“…They apparently also do vary between pH 6.5 and 7.0 and therefore can be expressed by the average value of AHt=298 15 kcal mol-' (1247 2 63 kJ mol-I). This transi- tion enthalpy is appreciably higher than the enthalpy values reported so far for tRNAYhe (yeast), but its magnitude is in excellent agreement with melting enthalpies recently determined for tRNA"' (yeast) and tRNASe' (yeast) [25]. Partial specific heat capacities normalized to 20 "C [ c i ]~~, are also consistent for these three tRNA's.…”
Section: Resultssupporting
confidence: 53%
“…The overall tertiary structure is stabilized by specific Mg 2+ binding, which decreases electrostatic repulsion where four RNA strands converge [19][20][21][22][23]. Thermodynamic studies have shown that the tRNA structure is highly stable, and cooperatively unfolds in the absence of Mg 2+ [24][25][26][27][28][29][30][31]. Modified nucleotides, while not required for tRNA conformation, contribute to the stability of tRNA folding [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…A striking feature of several of the tRNA Gln species with inserted class II variable domains is a distinctive thermodynamic signature as shown by thermal melting analysis (Fig+ 3A)+ Replotting the melting curves as first derivative plots (Fig+ 3B) shows that one transition at approximately 64 8C is greatly enhanced for tRNA QSer , tRNA QSer_C44 , and tRNA QSer_C9/A13 relative to G1-tRNA Gln and tRNA QSer_2D + It is well established that in the absence of Mg 2ϩ , tRNAs unfold in stages over a very broad temperature range (Cole et al+, 1972;Yang & Crothers, 1972;Crothers et al+, 1974;Filimonov et al+, 1976;Privalov & Filimonov, 1978)+ Four to five separate transitions have been identified, and assigned via NMR and temperature-jump kinetics to the melting of different helices+ While several of these studies examined both class I and class II tRNA species, no specific features of the melting curves were assigned to the presence of the extra arm, and the class II tRNAs did not show enhanced thermostability+ Therefore, the better-defined and apparently more cooperative transitions in tRNA QSer and several of its derivatives appear not to be a general distinguishing characteristic of class I versus class II tRNAs+ Further, because all of the melting transitions in tRNA are known and correspond to the helical stems and tertiary core region, the 59-and 39-end heterogeneity in the transcripts cannot significantly influence the observed profiles+ No differences in the structures of the acceptor, D, anticodon, or T stems exist between tRNA Gln and tRNA QSer + The distinct melting curves of these species must therefore arise from either the particularly large variable stem-loop in tRNA QSer , or from a very stable structure produced at the junction of the variable stem with the core region+ It should also be noted that the tRNAs were prepared for melting analysis by dialysis into a buffer lacking Mg 2ϩ cations, after refolding in the presence of 10 mM MgSO 4 + Possibly, tRNA QSer , tRNA QSer_C44, and tRNA QSer_C9/A13 possess a tight Mg 2ϩ binding site from which the metal is not removed by dialysis, and which is either not present or is weakened in G1-tRNA Gln and tRNA QSer_2D + Regardless of the detailed rationale for the distinct behaviors, however, the melting analysis provides a convenient solution assay, independent of function in aminoacylation, which reports on whether derivative species possess the particular tertiary structure of tRNA QSer + The 2-nt insertion in the D-loop, missing in tRNA QSer_2D , is evidently essential to stabilizing some aspect of the tertiary structure of tRNA QSer (Fig+ 3)+ This is consistent with the crystal structures, since deletion of these nucleotides removes the "platform" base G20b upon which the proximal base pair of the variable stem rests (Fig+ 1)+ Because tRNA QSer_2D is as stable as the class I G1-tRNA Gln , this analysis also suggests that the variable stem-loop may function as an independent folding domain in class II tRNAs+ Its destabilization (or the destabilization of a structural element closely linked to it) does not result in global unfolding of the molecule+…”
Section: Tertiary Structure Stability Of Class II Trnasmentioning
confidence: 98%